Preparation and characterization of adenine-based polyimide/nano-silica hybrid films. (May 2018) - Lu, Zheng; Hu, Jiang-Huai; Chen, Chang; Peng, Wei-Feng; Liu, Zheng-Zhou; Liu, Yang; Zeng, Ke; Yang, Gang
Graphical abstract: Abstract: To broaden the application of polyimide materials, adenine-based polyimide/nano-silica hybrid films were prepared via sol-gel method without using coupling agents. Adenine-based diamine, 9, 10-bis(4-aminopheny)adenine ( p -APA), was introduced to polymerize with 3, 3′, 4, 4′-tetracarboxydiphthalic ether dianhydride (ODPA) to synthesize polyimide (API) matrix. The compatibility between the polymer matrix and silica was improved by hydrogen bonding between NH group in p -APA and SiOH group in silica. Systematic studies showed that API hybrid films possess high transparency and outstanding thermal properties even though the doping content was up to 20 wt% (glass transition temperature ( Tg ): 328 °C, maximum decomposition occurring temperature ( Tmax ): 603 °C (N2 ), coefficient of thermal expansion (CTE): 16.60 ppm/ o C).